On the kinetics of catalytic hydrogenation over Pd nanoparticles regulated by various nucleosides. (29th June 2019) - Wang, Tengda; Shan, Jianxing; Wang, Li; Zhang, Xiangwen; Li, Guozhu
Graphical abstract: Highlights: Nucleosides and their derivatives are used to regulate Pd NPs for hydrogenation. Activity of Pd NPs is correlated with the structure of capping agent. Kinetics of hydrogenation on the Pd NPs regulated by nucleosides has been studied. Abstract: Aqueous-phase hydrogenation of 4-nitrophenol (4-NIP) by H2 has been investigated in the presence of Pd nanoparticles (NPs) regulated by small biological molecules. Nucleosides and their derivatives were employed as capping agents of Pd NPs, and their effect on Pd activity was evaluated. All four kinds of nucleosides exhibited obvious promoting effect on the activity of Pd NPs in comparison to that without any capping agent. The general promoting effect sequence of nucleosides and their derivatives on the activity of Pd NPs was nucleoside ≥ nucleotide > deoxynucleoside > base > deoxynucleotide. The quantitative correlation between the activity promoting effect and the structure of nucleosides and their derivatives were also studied using the method based on poly-parameter linear free energy relationships. Moreover, the kinetic behaviors of 4-NIP hydrogenation over Pd NPs regulated by different nucleosides (adenosine, guanosine, cytidine, and β-thymidine) were studied systematically and different kinetic models were developed to fit the data. The obtained kinetic data fitted well to the Langmuir-Hinshelwood (L-H) model, where the surface reaction is the rate-controlling step. The apparent activation energy, adsorption enthalpy of 4-NIP, and dissociated adsorption enthalpy of hydrogen were calculated and compared for a better understanding of the mechanism. Pd NPs regulated by cytidine showed the lowest apparent activation energy of 43.66 kJ mol −1 .